2018
DOI: 10.1002/cpt.971
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment Strategies in Pediatric Drug Development: An Analysis of Trials Submitted to the US Food and Drug Administration

Abstract: Clinical trial enrichment involves prospectively incorporating trial design elements that increase the probability of detecting a treatment effect. The use of enrichment strategies in pediatric drug development has not been systematically assessed. We analyzed the use of enrichment strategies in pediatric trials submitted to the US Food and Drug Administration from 2012-2016. In all, 112 efficacy studies associated with 76 drug development programs were assessed and their overall success rates were 78% and 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Patient selection criteria and enrichment of the pediatric study population are additional considerations for trial success, and a recent review of pediatric enrichment has been published. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient selection criteria and enrichment of the pediatric study population are additional considerations for trial success, and a recent review of pediatric enrichment has been published. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Patient selection criteria and enrichment of the pediatric study population are additional considerations for trial success, and a recent review of pediatric enrichment has been published. 26 Although our cohort contained more than 200 trials, this should be considered an exploratory analysis because of the relatively small numbers of trials in some therapeutic areas. It can also be difficult to determine any one isolated reason why a trial may have failed, and there are often multiple factors contributing to trial outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of pediatric product development trials of triptans for treatment of migraines, a systematic review by Sun et al 1 suggested that utilizing enrichment strategies is a way to overcome the challenge of a true high placebo response rate in pediatric patients. 18 The report found that applying the nonrandomization of patients with an early placebo response have produced successful reductions in the high placebo response rate in the pediatric population and led to product (rizatriptan) approval by the FDA for a pediatric migraine indication. Other reasonable approaches are (1) combined trials 19 with a separate subgroup analysis and (2) a composite endpoint that includes both subjective and objective components.…”
Section: Discussionmentioning
confidence: 99%
“…Including biomarkers in development plans has been associated with greater success rates across therapeutic areas [15, 21, 87]. The use of several types of biomarkers (predictive, prognostic) in development programs is associated with higher success rates in trials compared to trials with no or few biomarkers [88]. The “right” biomarker varies by the type of information needed to inform a development program and the specific phase of drug development.…”
Section: The Right Biomarkermentioning
confidence: 99%